1978
DOI: 10.1111/j.1432-1033.1978.tb12562.x
|View full text |Cite
|
Sign up to set email alerts
|

Histidine in the Nucleotide‐Binding Site of NADP‐Linked Isocitrate Dehydrogenase from Pig Heart

Abstract: Incubation of pig heart NADP-dependent isocitrate dehydrogenase with ethoxyformic anhydride (diethylpyrocarbonate) at pH 6.2 results in a 9-fold greater rate of loss of dehydrogenase than of oxalosuccinate decarboxylase activity. The rate constants for loss of dehydrogenase and decarboxylase activities depend on the basic form of ionizable groups with pk' values of 5.67 and 7.05, respectively, suggesting that inactivation of the two catalytic functions results from reaction with different amino acid residues. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
23
0

Year Published

1981
1981
1999
1999

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 31 publications
7
23
0
Order By: Relevance
“…Our results also showed the absence of an essential reactive cysteine residue at the active site of this enzyme. The second‐order rate constant ( k 2 ) for inactivation of the enzyme by DEPC, 3 m −1 ·s −1 (180 m −1 · min −1 ) at pH 6.5 is within the range of the values obtained for the reaction of DEPC with histidine residues of different enzymes (10–1800 m −1 ·min −1 at pH 6 and 25 °C) or with the imidazole ring in model compounds (150–200 m −1 ·min −1 ) [37,40]. For pig‐heart NADP‐isocitrate dehydrogenase the value of this constant is 200 m −1 ·min −1 at pH 6.0.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…Our results also showed the absence of an essential reactive cysteine residue at the active site of this enzyme. The second‐order rate constant ( k 2 ) for inactivation of the enzyme by DEPC, 3 m −1 ·s −1 (180 m −1 · min −1 ) at pH 6.5 is within the range of the values obtained for the reaction of DEPC with histidine residues of different enzymes (10–1800 m −1 ·min −1 at pH 6 and 25 °C) or with the imidazole ring in model compounds (150–200 m −1 ·min −1 ) [37,40]. For pig‐heart NADP‐isocitrate dehydrogenase the value of this constant is 200 m −1 ·min −1 at pH 6.0.…”
Section: Discussionsupporting
confidence: 68%
“…In the presence of 5 m urea (data not shown), the number of total histidine residues/subunit of C. acremonium NADP‐isocitrate dehydrogenase was estimated to be eight. For the pig‐heart enzyme, Ehrlich and Colman [37] reported a total number of 14 histidine residues modified by DEPC.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The technique of affinity labeling, using nucleotide analogues with reactive functional groups, can potentially result in more tThis work was supported by USPHS Grant DK 39075. specific chemical modification and should allow the identification of critical amino acid residues within the nucleotide binding site (Colman, 1983b). Studies of the binding of coenzymes and coenzyme fragments to NADP+-specific isocitrate dehydrogenase have demonstrated that a 2,-phosphate is essential for the enzyme-nucleotide interaction (Ehrlich & Colman, 1978;Mas & Colman, 1985), suggesting that any potential affinity label for this enzyme retain the 2'-phosphate.…”
mentioning
confidence: 99%